SOME ASPECTS OF AUDITING ACCOUNTS RECEIVABLE AT ENTERPRISES - Rizakulov Abdurauf Abdimutalibovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article discusses some aspects of auditing accounts receivable. The essence of the concept of accounts receivable is studied. Proposals and recommendations are developed to improve the audit of accounts receivable at enterprises.